Principles of turbomachinery - Turton, R. K. (London E. & F. N. Spon, 1984)
Pumps, fans, compressors and turbines are essential components in all engineering complexes. This book explains the basic fluid mechanics and thermodynamics underlying their design in a clear and uncomplicated way, with many examples and worked examples. It deals thoroughly with problems such as cavitation, refers to computer-based exercises wherever possible and provides up-to-date information on rapid advances currently being made in analysis and performance control.
Keywords: Turbomachines